2020
DOI: 10.1186/s13601-020-00335-w
|View full text |Cite
|
Sign up to set email alerts
|

AllergoOncology: ultra-low IgE, a potential novel biomarker in cancer—a Position Paper of the European Academy of Allergy and Clinical Immunology (EAACI)

Abstract: Elevated serum IgE levels are associated with allergic disorders, parasitosis and specific immunologic abnormalities. In addition, epidemiological and mechanistic evidence indicates an association between IgE-mediated immune surveillance and protection from tumour growth. Intriguingly, recent studies reveal a correlation between IgE deficiency and increased malignancy risk. This is the first review discussing IgE levels and links to pathological conditions, with special focus on the potential clinical signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 170 publications
(267 reference statements)
2
43
0
Order By: Relevance
“…Furthermore, it has been shown that there were no significant differences between the number of FcεRI receptors on monocytes in healthy volunteers and allergic patients [15]. Interestingly, recent reports suggest that patients with IgE deficiency have higher risk of developing malignancies [48,49]. It is possible that IgE deficient patients with cancer, whose IgE receptors may be mostly unoccupied, may also benefit from treatment with tumour antigen-specific IgE immunotherapy to prompt immune cell activation and cytotoxic killing of target tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that there were no significant differences between the number of FcεRI receptors on monocytes in healthy volunteers and allergic patients [15]. Interestingly, recent reports suggest that patients with IgE deficiency have higher risk of developing malignancies [48,49]. It is possible that IgE deficient patients with cancer, whose IgE receptors may be mostly unoccupied, may also benefit from treatment with tumour antigen-specific IgE immunotherapy to prompt immune cell activation and cytotoxic killing of target tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Very low or absent IgE was shown to impede anti-tumour surveillance and there is evidence that ultra-low IgE might serve as a biomarker for cancer risk. 62 Nevertheless, hitherto existing data from omalizumab in clinical studies and post-marketing do not indicate striking incidence rates for malignancies, such as non-melanoma skin cancer. 63 Indeed, a recent systematic review and meta-analysis reported that patients receiving long-term omalizumab were not significantly more likely to develop study-emergent solid epithelial cancer than those receiving standard treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, ultra-low IgE is likely to be an unexpected biomarker for cancer risk. Even in this study, the authors suggest the need for in-depth mechanistic studies and cancer risk stratification based on demographic and immunological characteristics and possible clinical cofactors ( 5 ).…”
mentioning
confidence: 88%